Reliable Smart Pet Feeding Machine Using Arduino Uno Starter Kit - M.S.Z.M, Suffian; A.N.H.A, zaini; Annisa, Binti Jamali; Shahrol, Mohamaddan; Muhd Fadzli, Ashari (2021)
Pet feeding can be done manually by pet owners, or automatically with the help of the pet feeders. The main concerns here are to solve the issue of unavailability of pet owners and the hygiene aspect in pet feeding. The developed automated system enables pet owners to feed their pets while they are away. The main objective of operating this research is to develop an automated pet feeding device focusing on in house pets by utilizing Arduino Uno as its Central Processing Unit (CPU) or microcontroller which function to control a weight sensor (load cells) and a servo motor. Smart Pet Feeding Machine is an automated pet feeding device designed to run based on weight mechanism. It will automatically dispense pet foods when minimum amount of pet food weight is triggered and will automatically stop dispensing when it reaches maximum amount of weight. Its architectural design includes a vertical storage compartment to store pet foods, a square opening at the bottom of storage compartment as opening for dispensing, a motorized dispenser and an aluminium bowl to place dispensed pet foods. The motion of dispenser is operated by a servo motor attached to the dispenser.